2011
DOI: 10.1038/cdd.2011.89
|View full text |Cite
|
Sign up to set email alerts
|

The miR 302-367 cluster drastically affects self-renewal and infiltration properties of glioma-initiating cells through CXCR4 repression and consequent disruption of the SHH-GLI-NANOG network

Abstract: Glioblastoma multiforme (GBM) is the most common form of primary brain tumor in adults, often characterized by poor survival. Glioma-initiating cells (GiCs) are defined by their extensive self-renewal, differentiation, and tumor initiation properties. GiCs are known to be involved in tumor growth and recurrence, and in resistance to conventional treatments. One strategy to efficiently target GiCs in GBM consists in suppressing their stemness and consequently their tumorigenic properties. In this study, we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
129
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(139 citation statements)
references
References 37 publications
8
129
0
2
Order By: Relevance
“…These aberrantly expressed miRNAs play essential roles in the regulation of TIC properties as either TIC suppressors or promoters [20][21][22][23][24] . Moreover, a series of critical signalling pathways involved in the regulation of TIC properties have been uncovered with the identification of the targets of these miRNAs 19,[25][26][27][28] . Importantly, miRNAs are also demonstrated to be promising biomarkers and amenable therapeutic targets 5,19,24 .…”
mentioning
confidence: 99%
“…These aberrantly expressed miRNAs play essential roles in the regulation of TIC properties as either TIC suppressors or promoters [20][21][22][23][24] . Moreover, a series of critical signalling pathways involved in the regulation of TIC properties have been uncovered with the identification of the targets of these miRNAs 19,[25][26][27][28] . Importantly, miRNAs are also demonstrated to be promising biomarkers and amenable therapeutic targets 5,19,24 .…”
mentioning
confidence: 99%
“…4 miRNA dysregulation is a common feature of neoplasia and numerous miRNAs have been characterized as oncogenes or tumor suppressors in many cancers including in glioblastoma (GBM). 3,[5][6][7][8][9][10][11] microRNA-134 (miR-134) has been implicated in the regulation of physiological and developmental processes. It was shown to promote mouse embryonic stem-cell differentiation, dendritogenesis, and stage-specific cortical development.…”
mentioning
confidence: 99%
“…Up-regulation of miR-302/367 has been reported in glioblastoma multiforme. It is shown that this miR cluster is rapidly and strongly induced in glioma-initiating cells (Fareh et al, 2012). In addition, miR-302 is reported to be enriched in human leukaemia cell lines (Yu et al, 2006), large B cell lymphoma (Lawrie et al, 2009).…”
Section: B Amentioning
confidence: 99%